Assessment of incidence rate and prognosis of metabolic syndrome among acute myocardial infarction: a longitudinal study - Uppin, Archana M.; Badiger, Raju H.; Sharma, Gayatri; Soni, Rishab; Parne, Sowmya; Maddiri, Pavan Kumar (International Journal of Advances in Medicine, 2020)
Background: The Metabolic Syndrome (METS) is a specific clustering of cardiovascular risk factors in the same person (abdominal obesity, atherogenic dyslipidemia, elevated Blood Pressure (BP), Insulin Resistance (IR), and a proinflammatory state. A recent review of insulin resistance syndrome revealed a rapid escalation of this syndrome among Indians and the prevalence of predominant component of METS varies from region to region. Hence the present study was undertaken to assess the incidence of Metabolic Syndrome and prognosis of metabolic syndrome among acute myocardial infarction patients. Methods: A longitudinal study was carried among Acute myocardial infarction patients, who were admitted to ICCU of Shri. B. M. Patil Hospital and Research Centre, Bijapur during November 2009 to March 2011. Sample size was calculated using the formula: n=4pq/L2. Sample size required was 92. Descriptive statistics and Inferential statistics were used to analyse the results. Results: The incidence rate of METS among AMI in our study was 48.7%. The complications were more common in METS group compared to those without METS groups. Recovery was better among those without METS group. There was a statistically significant association between complications and status of METS. The past history of DM was more common in METS. Hyperglycemia among the components of METS has strongest association with the outcome of death in patients of AMI. Conclusions: The metabolic syndrome is a highly prevalent condition among the patients with acute myocardial infarction and has detrimental impact on outcome Metabolic syndrome is also associated with a higher risk of severe heart failure and death.